Perubahan Tutupan Lahan dan Pengaruhnya Terhadap Pola Persebaran Suhu di Kota Gorontalo - Mohammad Duka; Fitryane Lihawa; Sukirman Rahim (Jambura Geoscience Review, 2020)
Gorontalo City is one of the regions in Gorontalo Province. Urban development and population growth, causing pressure on land use patterns. Changes in land use are carried out to meet the community's needs for infrastructure. At present, development in Gorontalo City is still ongoing. The increase in temperature is expected to continue and can trigger heat island. This is very important to be studied for the Gorontalo City development planning that is more environmentally friendly. This study aims to analyze the heat island phenomenon through the relationship of the spatial distribution of surface temperature with various types of land cover and vegetation characteristics. The object of this research is the Gorontalo City area on Landsat path-row 121- 65 satellite imagery media. The research material is the wavelength of visible light, near-infrared and moderate infrared and thermal wavelengths on satellite imagery of Landsat TM and OLI TIRS. The results showed an increase in temperature in Gorontalo City since 1990, 2003, and 2017. The correlation between surface temperature and land cover is negative. The value of the correlation coefficient (r) in 1990 was -0.41. The correlation coefficient (r) in 2003 was -0.448. The correlation coefficient (r) in 2017 is -0.402. Changes in surface temperature in Gorontalo City are influenced by changes in the land cover which is marked by the similarity of patterns of changes in surface temperature distribution with patterns of land cover changes.